Penerapan Model Project Based Learning dalam Pembelajaran Menulis Teks Pawarta Kelas X SMAN 01 Tanjung Tahun Ajaran 2023-2024 - Mulyanti, Lisa Dewi; Alfiah, Alfiah; Werdiningsih, Yuli Kurniati (Piwulang Jurnal Pendidikan Bahasa Jawa, 2024)
Students' lack of interest in learning to write the text of the Class X newspaper depends on the completeness of the content (elements of the newspaper), spelling and punctuation, and structure of the newspaper. This study aims to describe the results of applying the project-based learning model in learning to write news texts for Class X students of SMA N 01 Tanjung in the 2023-2024 academic year. This study is included in the experimental research with the descriptive quantitative approach. The data obtained in this study were collected by observation (observation) and questionnaire (questionnaire), while purposive sampling was used. The type used in this study is a one-shot case study. After data analysis, the results of this study are as follows: 1) in the aspect of knowledge, there are 28 students, or 78%, who obtained scores above the KKM, while 8 students, or 22%, have not completed the KKM. From the percentage, the completeness of the value was obtained at 77.27. 2). In the aspect of skills, there were 30 students, or 83%, obtained grades above KKM, while 6 students, or 17%, had not reached KKM completeness. From the present, the completeness value was obtained by 81.33. Thus, applying the project-based learning model in learning to write news text for class X9 students can influence the achievement of the specified learning goals.